Vacuum in-tube extraction (V-ITEX): A tutorial review of theoretical principles, operational parameters, and applications - Lucie K. Tintrop; Simon Wacker; Florian Kopiec; Stefan Cretnik; Pascal Fuchsmann (Analytica Chimica Acta, 2026)

Heterospecific social behavior in primates: insights into the evolutionary roots of pet-keeping - Cyril C. Grueter; Fany Roncin; K. Anne-Isola Nekaris; Jill Pruetz; Richard McFarland; Sabit Hasan; Malgorzata Arlet; Timothy M. Eppley; Susan M. Cheyne; Vincent Nijman; Eckhard W. Heymann; Pascal R. Marty; et al. (Primates, 2026)
Primate interspecific interactions with both other primates and non-primate species range from predator–prey dynamics to affiliative behaviors such as grooming, play, and carrying. While many primates participate in interspecific associations or commensal relationships, to our knowledge interspecific social interactions have never been systematically synthesized. Here, we present the first comprehensive review of such interactions, compiling 427 cases from the literature, media sources, and a global survey of primatologists. These involved 88 primate species and 127 non-primate species (including mammals, birds, reptiles, amphibians, malacostracans, and insects) across wild (n = 311) and captive (n = 111) contexts. The most frequent interactions occurred within or between primate families (e.g., Cercopithecidae–Cercopithecidae, Cebidae–Atelidae), though affiliative behaviors were also directed toward distantly related taxa such as dogs and birds. Play (n = 139) and grooming (n = 136) were most common. Juveniles and infants predominantly engaged in play, while adult females were more likely to groom. Adult males were less affiliative overall. Contrary to expectations, affiliative behaviors were not more often directed toward immature than adult heterospecifics. Primates were the initiators in most interactions. These findings offer new insights into the diversity and contexts of heterospecific sociality in primates and suggest that some behavioral tendencies relevant to later forms of human–animal companionship – such as caregiving, tolerance, and exploratory play – may be more widespread among primates than previously recognized.

Influence of pillar plants in vegetation patches on soil carbon in hyperarid ecosystems of the AlUla region - Oscar Pascal Malou; Stéphane Boivin; Baptiste Kerfriden; David Sebag; Jérôme Nespoulous; Ines Ben Ammar; Hassan Boukcim; Yassine Fendane; Sami D. Almalki; Shauna K. Rees; Abdalsamad Aldabaa; Ahmed H. Mohamed; et al. (Journal of Arid Environments, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Frequent weak seismic shakings affect landslide occurrence and threaten 20% of Nepal’s population - Fang Chen; Bo Yu; Huadong Guo; Pascal Lacroix; Noélie Bontemps; Shengwen Qi; Umesh K. Haritashya; Jeffrey S. Kargel; Ni Huang; Lei Wang (Science Bulletin, 2026)

Dynamics of the inland penetrating Indian monsoon depressions - K Sandhyavijayan; K. P. Sooraj; E. Suhas; Pascal Terray (Climate Dynamics, 2026)

Genetic variation and population structure of the sorghum germplasm panel of Eastern Africa origin through DArTseq - Kiplagat Kurgat; Pascal P. Okwiri Ojwang; Erick K. Cheruiyot; Cathrine Ziyomo (Euphytica, 2026)

Impact of Human Activities and Forest Biomass on Atmospheric Carbon Dioxide: A Mathematical Model - David Mbelle Ngoh; Anjali Jha; Bring; A. K. Misra; Dany-Pascal Moualeu Ngangue; Louis Aimé Fono (Environmental Modeling & Assessment, 2025)

Adsorption of 4-bromophenol from simulated wastewater using magnetic carbon-based composites: Kinetics, equilibrium, thermodynamics, and density functional theory analysis - Beatris L. Mello; Pascal S. Thue; Ali Hamid; Muhammad Usama; Fernando Machado Machado; Moaaz K. Seliem; Younes Dehmani; Glaydson S. dos Reis; Mohamed Abdel Salam; Hammad Khan; Luis F.O. Silva; Eder C. Lima (Journal of Water Process Engineering, 2025)

Detailed analysis of olefins and diolefins in hydrotreated plastic waste pyrolysis oils by GC-VUV - Yannick Ureel; César Pernalete Piña; Melissa N. Dunkle; Pascal Pijcke; Bruno da Costa Magalhaes; Marvin Kusenberg; Georgios Bellos; Maarten K. Sabbe; Joris W. Thybaut; Kevin M. Van Geem (Waste Management, 2025)

How raw milk-based adjunct cultures influence microbial diversity in cheese - Matthias Dreier; Luca Bettera; Hélène Berthoud; Pascal Fuchsmann; Lucie K. Tintrop; Hans-Peter Bachmann; Dominik Guggisberg; Remo S. Schmidt (International Dairy Journal, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Infrared Nanoscopy and Tomography of Intracellular Structures - Joachim Heberle; Katerina Kanevche; David J. Burr; Dennis J. Nürnberg; Pascal K. Hass; Andreas Elsässer (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Correction: On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Global habitat predictions to inform spatiotemporal fisheries management: Initial steps within the framework - Heather D. Bowlby; Jean-Noël Druon; Jon Lopez; Maria José Juan-Jordá; María Teresa Carreón-Zapiain; Frederic Vandeperre; Agostino Leone; Brittany Finucci; Philippe S. Sabarros; Barbara A. Block; Haritz Arrizabalaga; Pedro Afonso; et al. (Marine Policy, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Efficacy of selected biopesticides on key pests of chilli pepper for increased productivity in Ghana - Médétissi Adom; Ken O. Fening; Maxwell K. Billah; Pascal O. Aigbedion-Atalor; David D. Wilson (Crop Protection, 2024)

On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Trawling-induced change in benthic effect trait composition – A multiple case study - Olivier Beauchard; Clare Bradshaw; Stefan Bolam; Justin Tiano; Clément Garcia; Emil De Borger; Pascal Laffargue; Mats Blomqvist; Irini Tsikopoulou; Nadia K. Papadopoulou; Christopher J. Smith; Jolien Claes; et al. (Frontiers in Marine Science, 2023)
Introduction The importance of the response-effect trait dichotomy in marine benthic ecology has garnered recent attention. Response traits, characterising species responses to environmental variations, have been a dominant focus in the development of ecological indicators for ecosystem health assessment. In contrast, effect traits, expressing effects of organism activities on the ecosystem, still do not benefit from an equal interest in spite of the complementary facet that they provide to complete our understanding of functional diversity and ecosystem vulnerability. In this study, we explore the consequences of disturbance by bottom trawl fisheries on benthic effect trait composition. Methods To this end, we used different contexts of environmental and trawling conditions from thirteen case studies in European waters and apply the same analytical procedure to derive a gradient that solely account for trawling-induced disturbance (Partial RLQ analysis). Results Bottom trawling was found to be a selective force of benthic effect trait composition in a majority of case studies. In general, tube-dwelling species were more typical of low trawling frequencies, whereas deep burrowing species were more resistant at high trawling frequencies. Although we report significantly deleterious effects of trawling on benthic ecosystem functions, the effect trait pattern along the gradient was never related to life span, a key response trait generally assumed to express recoverability following disturbance. Furthermore, we show that trends in species multi-functionality and community functional diversity can be negative or positive along the trawling intensity gradient. Discussion We discuss the relevance of these results in light of recent developments in the framework of response and effect trait dichotomy, and provide guidelines of trait data analysis in the context of trawl fisheries impact on the sea floor. Our findings emphasize the importance of fundamental concepts from functional ecology in this context and represent a first step toward an assessment of trawling effect more oriented on benthos-mediated biogeochemical processes.

Life in the fast lane: Revisiting the fast growth—High survival paradigm during the early life stages of fishes - Dominique Robert; Jun Shoji; Pascal Sirois; Akinori Takasuka; Ignacio A. Catalán; Arild Folkvord; Stuart A. Ludsin; Myron A. Peck; Su Sponaugle; Patricia M. Ayón; Richard D. Brodeur; Emily Y. Campbell; et al. (Fish and Fisheries, 2023)
Early life survival is critical to successful replenishment of fish populations, and hypotheses developed under the Growth‐Survival Paradigm (GSP) have guided investigations of controlling processes. The GSP postulates that recruitment depends on growth and mortality rates during early life stages, as well as their duration, after which the mortality declines substantially. The GSP predicts a shift in the frequency distribution of growth histories with age towards faster growth rates relative to the initial population because slow‐growing individuals are subject to high mortality (via starvation and predation). However, mortality data compiled from 387 cases published in 153 studies (1971–2022) showed that the GSP was only supported in 56% of cases. Selection against slow growth occurred in two‐thirds of field studies, leaving a non‐negligible fraction of cases showing either an absence of or inverse growth‐selective survival, suggesting the growth‐survival relationship is more complex than currently considered within the GSP framework. Stochastic simulations allowed us to assess the influence of key intrinsic and extrinsic factors on the characteristics of surviving larvae and identify knowledge gaps on the drivers of variability in growth‐selective survival. We suggest caution when interpreting patterns of growth selection because changes in variance and autocorrelation of individual growth rates among cohorts can invalidate fundamental GSP assumptions. We argue that breakthroughs in recruitment research require a comprehensive, population‐specific characterization of the role of predation and intrinsic factors in driving variability in the distribution and autocorrelation of larval growth rates, and of the life stage corresponding to the endpoint of pre‐recruited life.

Employ a Clay@TMSPDETA hybrid material as an adsorbent to remove textile dyes from wastewater effluents - Roberta A. Teixeira; Eder C. Lima; Antônio D. Benetti; Mu. Naushad; Pascal S. Thue; Beatris L. Mello; Glaydson S. dos Reis; Navid Rabiee; Dison Franco; Moaaz K. Seliem (Environmental Science and Pollution Research, 2023)

Stability of common bean (Phaseolus vulgaris L.) genotypes for root system architecture and seed yield in multi-environments - Binaissa U. Levene Castiano; Paul K. Kimurto; Pascal P. Okwiri Ojwang (Field Crops Research, 2023)

Anatomy of the Indian summer monsoon and ENSO relationship in a state-of-the-art CGCM: role of the tropical Atlantic Ocean - Pascal Terray; Ligin Joseph; K. P. Sooraj (Climate Dynamics, 2023)

Impact of bacterial strain acquisition in the lung of patients with COPD: the AERIS study - Lucio Malvisi; Aparna Yarraguntla; Marie-Cécile Mortier; Karen Osman; David W. Cleary; Béatrice Sente; Thierry G. Pascal; Vincent Weynants; Stuart C. Clarke; Laura Taddei; Tom M. A. Wilkinson; Jeanne-Marie Devaster; et al. (Infectious Diseases, 2022)

Composite of methyl polysiloxane and avocado biochar as adsorbent for removal of ciprofloxacin from waters - Roberta A. Teixeira; Eder C. Lima; Antônio D. Benetti; Pascal S. Thue; Diana R. Lima; Farooq Sher; Glaydson S. dos Reis; Navid Rabiee; Moaaz K. Seliem; Mohamed Abatal (Environmental Science and Pollution Research, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Killing two enemies with one stone? Genomics of resistance to two sympatric pathogens in Norway spruce - Hernán D. Capador‐Barreto; Carolina Bernhardsson; Pascal Milesi; Ingrid Vos; Karl Lundén; Harry X. Wu; Bo Karlsson; Pär K. Ingvarsson; Jan Stenlid; Malin Elfstrand (Molecular Ecology, 2021)
Trees must cope with the attack of multiple pathogens, often simultaneously during their long lifespan. Ironically, the genetic and molecular mechanisms controlling this process are poorly understood. The objective of this study was to compare the genetic component of resistance in Norway spruce to Heterobasidion annosum s . s . and its sympatric congener Heterobasidion parviporum . Heterobasidion root‐ and stem‐rot is a major disease of Norway spruce caused by members of the Heterobasidion annosum species complex. Resistance to both pathogens was measured using artificial inoculations in half‐sib families of Norway spruce trees originating from central to northern Europe. The genetic component of resistance was analysed using 63,760 genome‐wide exome‐capture sequenced SNPs and multitrait genome‐wide associations. No correlation was found for resistance to the two pathogens; however, associations were found between genomic variants and resistance traits with synergic or antagonist pleiotropic effects to both pathogens. Additionally, a latitudinal cline in resistance in the bark to H. annosum s . s . was found; trees from southern latitudes, with a later bud‐set and thicker stem diameter, allowed longer lesions, but this was not the case for H. parviporum . In summary, this study detects genomic variants with pleiotropic effects which explain multiple disease resistance from a genic level and could be useful for selection of resistant trees to both pathogens. Furthermore, it highlights the need for additional research to understand the evolution of resistance traits to multiple pathogens in trees.

Low dispersal and ploidy differences in a grass maintain photosynthetic diversity despite gene flow and habitat overlap - Jill K. Olofsson; Emma V. Curran; Florence Nyirenda; Matheus E. Bianconi; Luke T. Dunning; Vanja Milenkovic; Graciela Sotelo; Oriane Hidalgo; Robyn F. Powell; Marjorie R. Lundgren; Ilia J. Leitch; Patrik Nosil; et al. (Molecular Ecology, 2021)
Geographical isolation facilitates the emergence of distinct phenotypes within a single species, but reproductive barriers or selection are needed to maintain the polymorphism after secondary contact. Here, we explore the processes that maintain intraspecific variation of C 4 photosynthesis, a complex trait that results from the combined action of multiple genes. The grass Alloteropsis semialata includes C 4 and non‐C 4 populations, which have coexisted as a polyploid series for more than 1 million years in the miombo woodlands of Africa. Using population genomics, we show that there is genome‐wide divergence for the photosynthetic types, but the current geographical distribution does not reflect a simple habitat displacement scenario as the genetic clusters overlap, being occasionally mixed within a given habitat. Despite evidence of recurrent introgression between non‐C 4 and C 4 groups, in both diploids and polyploids, the distinct genetic lineages retain their identity, potentially because of selection against hybrids. Coupled with strong isolation by distance within each genetic group, this selection created a geographical mosaic of photosynthetic types. Diploid C 4 and non‐C 4 types never grew together, and the C 4 type from mixed populations constantly belonged to the hexaploid lineage. By limiting reproductive interactions between photosynthetic types, the ploidy difference probably allows their co‐occurrence, reinforcing the functional diversity within this species. Together, these factors enabled the persistence of divergent physiological traits of ecological importance within a single species despite gene flow and habitat overlap.

Infant Survival Among Free-Living Bonnet Macaques (Macaca radiata) in South India - Małgorzata E. Arlet; Krishna N. Balasubramaniam; Rajarshi Saha; Brianne Beisner; Pascal R. Marty; Stefano S. K. Kaburu; Eliza Bliss-Moreau; Ants Kaasik; Ullasa Kodandaramaiah; Brenda McCowan (International Journal of Primatology, 2021)
Female reproductive success depends to a large extent on infants’ ability to survive to maturity. While most studies of female reproductive success have focused on the effects of individuals’ sociodemographic factors (e.g., age/parity, dominance rank) on offspring survival among wild primates living in less disturbed habitats, little research has focused on offspring survival in urban or periurban animals. Here we investigated sociodemographic and anthropogenic determinants of infant survival (up to 1 yr of age) in free-ranging bonnet macaques ( Macaca radiata ) living in a periurban environment in Southern India. We conducted the study from November 2016 to May 2018, on two groups of bonnet macaques at the Thenmala tourist site in the state of Kerala. Fifty infants were born across two birth seasons. Of these infants, 29.2% died or disappeared in 2017 and 26.9% died or disappeared in 2018. We found that infant survival was strongly influenced by the mother’s parity: infants of experienced mothers had a better chance of survival than those of first-time mothers. We also found that male infants were more likely to die than female infants. However, we found no effects of mothers’ dominance rank, or of frequency of mothers’ interactions with humans and time spent foraging on anthropogenic food, on infant survival. Our results, consistent with findings from other wild primate species, show that even in challenging human-impacted environments, experienced bonnet macaque mothers have greater success than inexperienced ones.

Understanding global teleconnections to surface air temperatures in Japan based on a new climate classification - Pascal Oettli; Masami Nonaka; Masahiko Kuroki; Hiroyuki Koshiba; Yosuke Tokiya; Swadhin K. Behera (International Journal of Climatology, 2021)
Utilizing the self‐organizing map (SOM), a type of artificial neural network, a new classification of the climate of Japan is proposed. The SOM is applied on the monthly mean surface air temperature (SAT) anomalies, extracted from 762 stations. Considering the strong seasonal cycle in mid‐latitudes, the classification is performed for two distinct seasons, boreal winter and boreal summer. Applied on monthly average temperature, to capture the seasonal signal, the SOM is an easily implementable interesting tool to (a) objectively capture the patterns present in the input data, and (b) identify the source of interannual variability, which is crucial for power demand forecasting. While modulated by local conditions, SAT in Japan is mainly influenced by large‐scale circulation. It is found in this study that stronger relationships exist for tropics with southern regions and for extra‐tropics with northern regions, in the seasonally oriented teleconnection patterns. In winter, the regions are organized along a north–south orientation, with a secondary west–east orientation in the central part of the country. This organization is a function of the strength of the link with the tropical Pacific and Indian Oceans sea‐surface temperatures. Changes in the speed of the westerly jet, together with the modulation of the Western Pacific (WP)‐like and Eurasian (EU)‐like patterns, are also important for SAT in Japan in winter. In summer, the main organization follows a west–east orientation. The Pacific Japan (PJ)‐like pattern plays an important role in the geographical distribution of the SAT, together with the existence of mid‐latitude and subtropical wave trains, like the Silk Road (SR)‐like pattern.

Anatomy of the Indian Summer Monsoon and ENSO relationships in state-of-the-art CGCMs: role of the tropical Indian Ocean - Pascal Terray; K. P. Sooraj; Sébastien Masson; Chloé Prodhomme (Climate Dynamics, 2021)

Insect chemical ecology: chemically mediated interactions and novel applications in agriculture - Crispus M. Mbaluto; Pascal M. Ayelo; Alexandra G. Duffy; Anna L. Erdei; Anaїs K. Tallon; Siyang Xia; Gabriela Caballero-Vidal; Urban Spitaler; Magdolna O. Szelényi; Gonçalo A. Duarte; William B. Walker; Paul G. Becher (Arthropod-Plant Interactions, 2020)
Insect chemical ecology (ICE) evolved as a discipline concerned with plant–insect interactions, and also with a strong focus on intraspecific pheromone-mediated communication. Progress in this field has rendered a more complete picture of how insects exploit chemical information in their surroundings in order to survive and navigate their world successfully. Simultaneously, this progress has prompted new research questions about the evolution of insect chemosensation and related ecological adaptations, molecular mechanisms that mediate commonly observed behaviors, and the consequences of chemically mediated interactions in different ecosystems. Themed meetings, workshops, and summer schools are ideal platforms for discussing scientific advancements as well as identifying gaps and challenges within the discipline. From the 11th to the 22nd of June 2018, the 11th annual PhD course in ICE was held at the Swedish University of Agricultural Sciences (SLU) Alnarp, Sweden. The course was made up of 35 student participants from 22 nationalities (Fig. 1a) as well as 32 lecturers. Lectures and laboratory demonstrations were supported by literature seminars, and four broad research areas were covered: (1) multitrophic interactions and plant defenses, (2) chemical communication focusing on odor sensing, processing, and behavior, (3) disease vectors, and (4) applied aspects of basic ICE research in agriculture. This particular article contains a summary and brief synthesis of these main emergent themes and discussions from the ICE 2018 course. In addition, we also provide suggestions on teaching the next generation of ICE scientists, especially during unprecedented global situations.

Shared ancestral polymorphisms and chromosomal rearrangements as potential drivers of local adaptation in a marine fish - Hugo Cayuela; Quentin Rougemont; Martin Laporte; Claire Mérot; Eric Normandeau; Yann Dorant; Ole K. Tørresen; Siv Nam Khang Hoff; Sissel Jentoft; Pascal Sirois; Martin Castonguay; Teunis Jansen; et al. (Molecular Ecology, 2020)
Gene flow has tremendous importance for local adaptation, by influencing the fate of de novo mutations, maintaining standing genetic variation and driving adaptive introgression. Furthermore, structural variation as chromosomal rearrangements may facilitate adaptation despite high gene flow. However, our understanding of the evolutionary mechanisms impending or favouring local adaptation in the presence of gene flow is still limited to a restricted number of study systems. In this study, we examined how demographic history, shared ancestral polymorphism, and gene flow among glacial lineages contribute to local adaptation to sea conditions in a marine fish, the capelin ( Mallotus villosus ). We first assembled a 490‐Mbp draft genome of M. villosus to map our RAD sequence reads. Then, we used a large data set of genome‐wide single nucleotide polymorphisms (25,904 filtered SNPs) genotyped in 1,310 individuals collected from 31 spawning sites in the northwest Atlantic. We reconstructed the history of divergence among three glacial lineages and showed that they probably diverged from 3.8 to 1.8 million years ago and experienced secondary contacts. Within each lineage, our analyses provided evidence for large N e and high gene flow among spawning sites. Within the Northwest Atlantic lineage, we detected a polymorphic chromosomal rearrangement leading to the occurrence of three haplogroups. Genotype–environment associations revealed molecular signatures of local adaptation to environmental conditions prevailing at spawning sites. Our study also suggests that both shared polymorphisms among lineages, resulting from standing genetic variation or introgression, and chromosomal rearrangements may contribute to local adaptation in the presence of high gene flow.

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

Individuals in urban dwelling primate species face unequal benefits associated with living in an anthropogenic environment - Pascal R. Marty; Krishna N. Balasubramaniam; Stefano S. K. Kaburu; Josephine Hubbard; Brianne Beisner; Eliza Bliss-Moreau; Nadine Ruppert; Małgorzata E. Arlet; Shahrul Anuar Mohd Sah; Ahmad Ismail; Lalit Mohan; Sandeep K. Rattan; et al. (Primates, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: Persistence of High In Vivo Efficacy and Safety of Artesunate–Amodiaquine and Artemether–Lumefantrine as the First- and Second-Line Treatments for Uncomplicated Plasmodium falciparum Malaria 10 Years After Their Implementation in Gabon - Jacques M. Ndong Ngomo; Guy J. Ondzagha Megnie; Bridy Moutombi Ditombi; Jeanne V. Koumba Lengongo; Noé P. M’Bondoukwé; Christelle L. Offouga; Denise P. Mawili-Mboumba; Jean B. Lekana-Douki; Pascal Ringwald; Thierry Fandeur; Marielle K. Bouyou-Akotet (Acta Parasitologica, 2019)

Persistence of High In Vivo Efficacy and Safety of Artesunate–Amodiaquine and Artemether–Lumefantrine as the First- and Second-Line Treatments for Uncomplicated Plasmodium falciparum Malaria 10 Years After Their Implementation in Gabon - Jacques M. Ndong Ngomo; Guy J. Ondzagha Megnie; Bridy Moutombi Ditombi; Jeanne V. Koumba Lengongo; Noé P. M’Bondoukwé; Christelle L. Offouga; Denise P. Mawili-Mboumba; Jean B. Lekana-Douki; Pascal Ringwald; Thierry Fandeur; Marielle K. Bouyou-Akotet (Acta Parasitologica, 2019)
Purpose Artesunate–amodiaquine (AS–AQ) and artemether–lumefantrine (AL) have been widely used for the treatment of uncomplicated Plasmodium falciparum malaria since 2005 in Gabon. Since 2011, a rebound of malaria morbidity has been observed in this country, while no survey evaluating ACT efficacy was performed. During the same period, parasite resistance against artemisinin has been reported in Asia. The aim of this study was to assess the efficacy and tolerability of these two drugs in two sentinel sites of Gabon 10 years after their implementation. Methods Children aged from 12 to 144 months with uncomplicated malaria were recruited at the Regional Hospital of Melen, Libreville and in the Urban Health Center of Franceville between March 2014 and September 2015. The therapeutic efficacy was evaluated according to the WHO 2008 protocol of 28-day follow-up and PCR-uncorrected/corrected treatment outcomes were assessed. Results One hundred and eighty-five children (98 ASAQ and 89 AL) were followed up until day 28. The PCR-corrected ACPR was 98.9% for AS–AQ and 96.4% for AL. Late therapeutic failure rate was 3.6% and 1.1% for AL and AS–AQ, respectively ( p = 0.2). Adverse events and serious adverse events were rarely observed with both treatments. Conclusion AS–AQ and AL are still efficacious and well-tolerated for the treatment of uncomplicated malaria in Gabonese children.

New GJA8 variants and phenotypes highlight its critical role in a broad spectrum of eye anomalies - Fabiola Ceroni; Domingo Aguilera-Garcia; Nicolas Chassaing; Dorine Arjanne Bax; Fiona Blanco-Kelly; Patricia Ramos; Maria Tarilonte; Cristina Villaverde; Luciana Rodrigues Jacy da Silva; Maria Juliana Ballesta-Martínez; Maria Jose Sanchez-Soler; Richard James Holt; et al. (Human Genetics, 2019)

An exploration of the links between parasites, trophic ecology, morphology, and immunogenetics in the Lake Tanganyika cichlid radiation - Britta S. Meyer; Pascal I. Hablützel; Anna K. Roose; Melinda J. Hofmann; Walter Salzburger; Joost A. M. Raeymaekers (Hydrobiologia, 2019)

Modulations of the Indian summer monsoon by the hot subtropical deserts: insights from coupled sensitivity experiments - K. P. Sooraj; Pascal Terray; Sébastien Masson; Julien Crétat (Climate Dynamics, 2019)

Reproductive behavior of the marine gastropod Charonia seguenzae (Aradas & Benoit, 1870) in captivity - CHRYSA K. DOXA; ASPASIA STERIOTI; PASCAL DIVANACH; MAROUDIO KENTOURI (Mediterranean Marine Science, 2019)
The reproductive behavior of the gastropod Charonia seguenzae (Aradas & Benoit, 1870) was studied through the description of 19 copulation and 21 egg laying events of 134 wild individuals. Findings in the present study regarding a part of the reproduction temperature range (20 to 23oC) and the demonstration of maternal care provided important information on their biology, behavior and ecology. Furthermore, observed polyandry by the females and collaborative care of embryonic sacks, were two aspects of the species reproductive biology that pose new questions both at ecological and evolutionary level.

C 4 anatomy can evolve via a single developmental change - Marjorie R. Lundgren; Luke T. Dunning; Jill K. Olofsson; Jose J. Moreno‐Villena; Jacques W. Bouvier; Tammy L. Sage; Roxana Khoshravesh; Stefanie Sultmanis; Matt Stata; Brad S. Ripley; Maria S. Vorontsova; Guillaume Besnard; et al. (Ecology Letters, 2019)
C 4 photosynthesis is a complex trait that boosts productivity in warm environments. Paradoxically, it evolved independently in numerous plant lineages, despite requiring specialised leaf anatomy. The anatomical modifications underlying C 4 evolution have previously been evaluated through interspecific comparisons, which capture numerous changes besides those needed for C 4 functionality. Here, we quantify the anatomical changes accompanying the transition between non‐C 4 and C 4 phenotypes by sampling widely across the continuum of leaf anatomical traits in the grass Alloteropsis semialata . Within this species, the only trait that is shared among and specific to C 4 individuals is an increase in vein density, driven specifically by minor vein development that yields multiple secondary effects facilitating C 4 function. For species with the necessary anatomical preconditions, developmental proliferation of veins can therefore be sufficient to produce a functional C 4 leaf anatomy, creating an evolutionary entry point to complex C 4 syndromes that can become more specialised.

Consumer trophic positions respond variably to seasonally fluctuating environments - Bailey C. McMeans; Taku Kadoya; Thomas K. Pool; Gordon W. Holtgrieve; Sovan Lek; Heng Kong; Kirk Winemiller; Vittoria Elliott; Neil Rooney; Pascal Laffaille; Kevin S. McCann (Ecology, 2019)
The effects of environmental seasonality on food web structure have been notoriously understudied in empirical ecology. Here, we focus on seasonal changes in one key attribute of a food web, consumer trophic position. We ask whether fishes inhabiting tropical river–floodplain ecosystems behave as seasonal omnivores, by shifting their trophic positions in relation to the annual flood pulse, or whether they feed at the same trophic position all year, as much empirical work implicitly assumes. Using dietary data from the Tonle Sap Lake, Cambodia, and a literature review, we find evidence that some fishes, especially small piscivores, increased consumption of invertebrates and/or plant material during the wet season, as predicted. However, nitrogen stable isotope (δ 15 N) data for 26 Tonle Sap fishes, spanning a broader range of functional groups, uncovered high variation in seasonal trophic position responses among species (0 to ±0.52 trophic positions). Based on these findings, species respond to the flood pulse differently. Diverse behavioral responses to seasonality, underpinned by spatiotemporal variation at multiple scales, could be central for rerouting matter and energy flow in these dynamic ecosystems. Seasonally flexible foraging behaviors warrant further study given their potential influence on food web dynamics in a range of fluctuating environments.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Temperature-related mortality impacts under and beyond Paris Agreement climate change scenarios - Ana Maria Vicedo-Cabrera; Yuming Guo; Francesco Sera; Veronika Huber; Carl-Friedrich Schleussner; Dann Mitchell; Shilu Tong; Micheline de Sousa Zanotti Staglior Coelho; Paulo Hilario Nascimento Saldiva; Eric Lavigne; Patricia Matus Correa; Nicolas Valdes Ortega; et al. (Climatic Change, 2018)

Intrinsic precursors and timescale of the tropical Indian Ocean Dipole: insights from partially decoupled numerical experiment - Julien Crétat; Pascal Terray; Sébastien Masson; K. P. Sooraj (Climate Dynamics, 2018)

Synthesis of grafted natural pozzolan with 3-aminopropyltriethoxysilane: preparation, characterization, and application for removal of Brilliant Green 1 and Reactive Black 5 from aqueous solutions - Alfred G. N. Wamba; Eder C. Lima; Sylvere K. Ndi; Pascal S. Thue; Joseph G. Kayem; Fabiano S. Rodembusch; Glaydson S. dos Reis; Wagner S. de Alencar (Environmental Science and Pollution Research, 2017)

Indian Ocean and Indian summer monsoon: relationships without ENSO in ocean–atmosphere coupled simulations - Julien Crétat; Pascal Terray; Sébastien Masson; K. P. Sooraj; Mathew Koll Roxy (Climate Dynamics, 2017)

Pan-European inter-laboratory studies on a panel of in vitro cytotoxicity and pro-inflammation assays for nanoparticles - Jean-Pascal Piret; Olesja M. Bondarenko; Matthew S. P. Boyles; Martin Himly; Ana R. Ribeiro; Federico Benetti; Caroline Smal; Braulio Lima; Annegret Potthoff; Monica Simion; Elise Dumortier; Paulo Emilio C. Leite; et al. (Archives of Toxicology, 2017)

Genome biogeography reveals the intraspecific spread of adaptive mutations for a complex trait - Jill K. Olofsson; Matheus Bianconi; Guillaume Besnard; Luke T. Dunning; Marjorie R. Lundgren; Helene Holota; Maria S. Vorontsova; Oriane Hidalgo; Ilia J. Leitch; Patrik Nosil; Colin P. Osborne; Pascal‐Antoine Christin (Molecular Ecology, 2016)
Physiological novelties are often studied at macro‐evolutionary scales such that their micro‐evolutionary origins remain poorly understood. Here, we test the hypothesis that key components of a complex trait can evolve in isolation and later be combined by gene flow. We use C 4 photosynthesis as a study system, a derived physiology that increases plant productivity in warm, dry conditions. The grass Alloteropsis semialata includes C 4 and non‐C 4 genotypes, with some populations using laterally acquired C 4 ‐adaptive loci, providing an outstanding system to track the spread of novel adaptive mutations. Using genome data from C 4 and non‐C 4 A. semialata individuals spanning the species’ range, we infer and date past migrations of different parts of the genome. Our results show that photosynthetic types initially diverged in isolated populations, where key C 4 components were acquired. However, rare but recurrent subsequent gene flow allowed the spread of adaptive loci across genetic pools. Indeed, laterally acquired genes for key C 4 functions were rapidly passed between populations with otherwise distinct genomic backgrounds. Thus, our intraspecific study of C 4 ‐related genomic variation indicates that components of adaptive traits can evolve separately and later be combined through secondary gene flow, leading to the assembly and optimization of evolutionary innovations.

Late season pharmaceutical fate in wetland mesocosms with and without phosphorous addition - Pascal Cardinal; Julie C. Anderson; Jules C. Carlson; Jennifer E. Low; Jonathan K. Challis; Charles S. Wong; Mark L. Hanson (Environmental Science and Pollution Research, 2016)

The Variability of Refractivity in the Atmospheric Boundary Layer of a Tropical Island Volcano Measured by Ground-Based Interferometric Radar - G. Wadge; A. Costa; K. Pascal; C. Werner; T. Webb (Boundary-Layer Meteorology, 2016)

Sub-seasonal behaviour of Asian summer monsoon under a changing climate: assessments using CMIP5 models - K. P. Sooraj; Pascal Terray; Prince Xavier (Climate Dynamics, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Impacts of Indian and Atlantic oceans on ENSO in a comprehensive modeling framework - Pascal Terray; Sébastien Masson; Chloé Prodhomme; Mathew Koll Roxy; K. P. Sooraj (Climate Dynamics, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Ipsilateral resistance exercise prevents exercise-induced central sensitization in the contralateral limb: a randomized controlled trial - Mahdi Hosseinzadeh; Afshin Samani; Ole K. Andersen; Kazunori Nosaka; Lars Arendt-Nielsen; Pascal Madeleine (European Journal of Applied Physiology, 2015)

Validation of SWH and SSHA from SARAL/AltiKa Using Jason-2 and In-Situ Observations - Suchandra Aich Bhowmick; Rashmi Sharma; K. N. Babu; A. K. Shukla; Raj Kumar; R. Venkatesan; R. M. Gairola; Pascal Bonnefond; Nicolas Picot (Marine Geodesy, 2015)

Global warming and the weakening of the Asian summer monsoon circulation: assessments from the CMIP5 models - K. P. Sooraj; Pascal Terray; M. Mujumdar (Climate Dynamics, 2015)

Control of Vegetative to Reproductive Phase Transition Improves Biomass Yield and Simultaneously Reduces Lignin Content in Medicago truncatula - Million Tadege; Fang Chen; Jeremy Murray; Jiangqi Wen; Pascal Ratet; Michael K. Udvardi; Richard A. Dixon; Kirankumar S. Mysore (BioEnergy Research, 2015)

Parallel signatures of selection in temporally isolated lineages of pink salmon - L. W. Seeb; R. K. Waples; M. T. Limborg; K. I. Warheit; C. E. Pascal; J. E. Seeb (Molecular Ecology, 2014)
Studying the effect of similar environments on diverse genetic backgrounds has long been a goal of evolutionary biologists with studies typically relying on experimental approaches. Pink salmon, a highly abundant and widely ranging salmonid, provide a naturally occurring opportunity to study the effects of similar environments on divergent genetic backgrounds due to a strict two‐year semelparous life history. The species is composed of two reproductively isolated lineages with overlapping ranges that share the same spawning and rearing environments in alternate years. We used restriction‐site‐associated DNA ( RAD ) sequencing to discover and genotype approximately 8000 SNP loci in three population pairs of even‐ and odd‐year pink salmon along a latitudinal gradient in North America. We found greater differentiation within the odd‐year than within the even‐year lineage and greater differentiation in the southern pair from Puget Sound than in the northern Alaskan population pairs. We identified 15 SNP s reflecting signatures of parallel selection using both a differentiation‐based method ( BAYESCAN ) and an environmental correlation method ( BAYENV ). These SNP s represent genomic regions that may be particularly informative in understanding adaptive evolution in pink salmon and exploring how differing genetic backgrounds within a species respond to selection from the same natural environment.

Translocation and turnover of rhizodeposit carbon within soil microbial communities of an extensive grassland ecosystem - Wajira K. Balasooriya; Karolien Denef; Dries Huygens; Pascal Boeckx (Plant and Soil, 2014)

Transformation of Althaea officinalis L. by Agrobacterium rhizogenes for the production of transgenic roots expressing the anti-HIV microbicide cyanovirin-N - Pascal M. W. Drake; Luisa de Moraes Madeira; Tim H. Szeto; Julian K-C. Ma (Transgenic Research, 2013)

Pain sensitivity is normalized after a repeated bout of eccentric exercise - Mahdi Hosseinzadeh; Ole K. Andersen; Lars Arendt-Nielsen; Pascal Madeleine (European Journal of Applied Physiology, 2013)

Temporal variation of rhizodeposit-C assimilating microbial communities in a natural wetland - Wajira K. Balasooriya; Dries Huygens; Karolien Denef; Dries Roobroeck; Niko E. C. Verhoest; Pascal Boeckx (Biology and Fertility of Soils, 2013)

Declaration of concern—an unambiguous rebuttal of the LEO-SCS-002 draft standard - Christoph Koffler; Jon Dettling; Cashion East; Matthias Finkbeiner; Sergio F. Galeano; Roland Geyer; Mark J. Goedkoop; Troy R. Hawkins; Connie D. Hensler; Arpad Horvath; Sebastien Humbert; Scott M. Kaufman; et al. (The International Journal of Life Cycle Assessment, 2013)

Eccentric exercise inhibits the H reflex in the middle part of the trapezius muscle - Steffen Vangsgaard; Lars T. Nørgaard; Brian K. Flaskager; Karen Søgaard; Janet L. Taylor; Pascal Madeleine (European Journal of Applied Physiology, 2013)

The role of the intra-daily SST variability in the Indian monsoon variability and monsoon-ENSO–IOD relationships in a global coupled model - Pascal Terray; Kakitha Kamala; Sébastien Masson; Gurvan Madec; A. K. Sahai; Jing-Jia Luo; Toshio Yamagata (Climate Dynamics, 2012)

Can the shrub Chromolaena odorata (Asteraceae) be considered as improving soil biology and plant nutrient availability? - Armand W. Koné; Ettien F. Edoukou; Jean T. Gonnety; Aurélie N. A. N’Dri; Laurenza F. E. Assémien; Pascal K. T. Angui; Jérôme E. Tondoh (Agroforestry Systems, 2012)

Possible role of warm SST bias in the simulation of boreal summer monsoon in SINTEX-F2 coupled model - Susmitha Joseph; A. K. Sahai; B. N. Goswami; Pascal Terray; Sebastian Masson; J.-J. Luo (Climate Dynamics, 2012)

Comparative study of earthworm communities, microbial biomass, and plant nutrient availability under 1-year Cajanus cajan (L.) Millsp and Lablab purpureus (L.) Sweet cultivations versus natural regrowths in a guinea savanna zone - Armand W. Koné; Ettien F. Edoukou; Jérôme E. Tondoh; Jean T. Gonnety; Pascal K. T. Angui; Dominique Masse (Biology and Fertility of Soils, 2012)

EAF2 loss enhances angiogenic effects of Von Hippel-Lindau heterozygosity on the murine liver and prostate - Laura E. Pascal; Junkui Ai; Lora H. Rigatti; Anne K. Lipton; Wuhan Xiao; James R. Gnarra; Zhou Wang (Angiogenesis, 2011)

Generation of transgenic plants expressing plasma membrane-bound antibodies to the environmental pollutant microcystin-LR - Tommaso Barbi; Pascal M. W. Drake; Matthew Drever; Craig J. van Dolleweerd; Andrew R. Porter; Julian K-C. Ma (Transgenic Research, 2011)

Optimisation of contained Nicotiana tabacum cultivation for the production of recombinant protein pharmaceuticals - Richard Colgan; Christopher J. Atkinson; Matthew Paul; Sally Hassan; Pascal M. W. Drake; Amy L. Sexton; Simon Santa-Cruz; David James; Keith Hamp; Colin Gutteridge; Julian K-C. Ma (Transgenic Research, 2010)

A benchmark study on problems related to CO2 storage in geologic formations - Holger Class; Anozie Ebigbo; Rainer Helmig; Helge K. Dahle; Jan M. Nordbotten; Michael A. Celia; Pascal Audigane; Melanie Darcis; Jonathan Ennis-King; Yaqing Fan; Bernd Flemisch; Sarah E. Gasda; et al. (Computational Geosciences, 2009)

Invasive rats and seabirds after 2,000 years of an unwanted coexistence on Mediterranean islands - L. Ruffino; K. Bourgeois; E. Vidal; C. Duhem; M. Paracuellos; F. Escribano; P. Sposimo; N. Baccetti; M. Pascal; D. Oro (Biological Invasions, 2009)

Is soil quality improvement by legume cover crops a function of the initial soil chemical characteristics? - Armand W. Koné; Jérôme E. Tondoh; Pascal K. T. Angui; France Bernhard-Reversat; Gladys Loranger-Merciris; Didier Brunet; Soumaïla T. K. Brédoumi (Nutrient Cycling in Agroecosystems, 2008)

A mutation in KIR3DS1 that results in truncation and lack of cell surface expression - Maureen P. Martin; Véronique Pascal; Meredith Yeager; John Phair; Gregory D. Kirk; Keith Hoots; Stephen J. O’Brien; Stephen K. Anderson; Mary Carrington (Immunogenetics, 2007)

A mutation in KIR3DS1 that results in truncation and lack of cell surface expression - Maureen P. Martin; Véronique Pascal; Meredith Yeager; John Phair; Gregory D. Kirk; Keith Hoots; Stephen J. O’Brien; Stephen K. Anderson; Mary Carrington (Immunogenetics, 2007)

A mutation in KIR3DS1 that results in truncation and lack of cell surface expression - Maureen P. Martin; Véronique Pascal; Meredith Yeager; John Phair; Gregory D. Kirk; Keith Hoots; Stephen J. O’Brien; Stephen K. Anderson; Mary Carrington (Immunogenetics, 2007)

Confirmation and dissection of QTL controlling resistanceto malaria in mice - Maria Hernandez-Valladares; Jan Naessens; John P. Gibson; Anthony J. Musoke; Sonal Nagda; Pascal Rihet; Onesmo K. ole-MoiYoi; Fuad A. Iraqi (Mammalian Genome, 2004)

Mapping of a new quantitative trait locus for resistance to malaria in mice by a comparative mapping approach with human Chromosome 5q31-q33 - Maria Hernandez-Valladares; Pascal Rihet; Onesmo K. ole-MoiYoi; Fuad A. Iraqi (Immunogenetics, 2004)

Rhizosecretion of a monoclonal antibody protein complex from transgenic tobacco roots - Pascal M.W. Drake; Daniel M. Chargelegue; Nicholas D. Vine; Craig J. van Dolleweerd; Patricia Obregon; Julian K-C. Ma (Plant Molecular Biology, 2003)

Assembly and plasma membrane targeting of recombinant immunoglobulin chains in plants with a murine immunoglobulin transmembrane sequence - Nicholas D. Vine; Pascal Drake; Andrew Hiatt; Julian K.-C. Ma (Plant Molecular Biology, 2001)

A murine monoclonal antibody produced in transgenic plants with plant-specific glycans is not immunogenic in mice - Daniel Chargelegue; Nicholas D. Vine; Craig J. van Dolleweerd; Pascal M.W. Drake; Julian K-C. Ma (Transgenic Research, 2000)

Modern pollen spectra from tropical South India and Sri Lanka: altitudinal distribution - R. Bonnefille; K. Anupama; D. Barboni; J. Pascal; S. Prasad; J. P. Sutra (Journal of Biogeography, 1999)
Summary We analysed the pollen content of 106 surface soil samples from evergreen and deciduous tropical forests distributed between 6° and 13° of latitude north in South India and Sri Lanka. The samples were collected along altitudinal gradients, ranging from 50 to 2420 m, in five regions that experience different rainfall regimes. Original pollen data from tropical vegetation subjected to seasonal monsoon rains are presented along altitude/temperature gradients. This paper includes a summarized description of the vegetation types mapped in the area. The pollen results are presented in the form of quantitative pollen diagrams and correspondence analyses. They show clear distinct pollen assemblages and markers for all types of vegetation in deciduous and evergreen vegetation. Forests are well identified by percentages of Arboreal Pollen greater than 50%, despite the fact that Dipterocarpaceae and Lauraceae are hardly recorded by pollen. The pollen distinction between low, medium and high elevation evergreen forests matches that established by ecologists. The botanical limits, respectively, placed at 900 m and 1500 m limits, correspond to the 20 °C and 15 °C‐values of mean temperature of the coldest month. They appear clearly identified in the modern pollen record. This justifies further use of pollen data in Biome modelling.

Molecular Mechanisms of the Adsorption of a Model Protein (Human Serum Albumin) on Poly(Methylidene Malonate 2.1.2) Nanoparticles - Yoléne Bousquet; Pieter J. Swart; Nathalie Schmitt-Colin; Florence Velge-Roussel; Mirjam E. Kuipers; Dirk K. F. Meijer; Nicole Bru; Johan Hoebeke; Pascal Breton (Pharmaceutical Research, 1999)

Nutrient relations in calcareous grassland under elevated CO 2 - Pascal A. Niklaus; Paul W. Leadley; Jrg Stcklin; Christian Krner (Oecologia, 1998)